O NOVO COMPORTAMENTO DO TELESPECTADOR EM UMA TELEVISÃO EM CONSTANTE MUDANÇA: IMPACTOS, CONEXÕES SOCIAIS E CONSUMO MIDIÁTICO - Miranda, Mozarth (LINKSCIENCEPLACE, 2026)
The expansion of the Internet and the emergence of Information and Communication Technologies - ICTs - have highlighted the need to think, and new products for Brazilian television. The challenges of this new way of communication to identify three areas of great discussion in academic , government and business means : Technology ; policy and creation of symbolic goods ( content ) , covering the broadcast standards ; and a standardization policy . The impact on viewer habits and consumption because of the options that should arise can influence the viewer's everyday life. One change is the increase in hours per day connected . The speed of information and the search for news team made more dependent on individual network . The vehicles are guided by it . And there, the characters are interacting with a network of connections and this field if feeds back to content (text or audiovisual ) and exchanges between the collaborative agents.